Kahoot! vs Quizizz in EFL Grammar Instruction: Comparative Effects on Immediate Recall, Delayed Retention, and Learner Engagement - Effendi Limbong (Barkah Publishing, 2026)
Kahoot! and Quizizz are among the most widely adopted game-based response platforms in EFL classrooms globally, yet direct comparative evidence of their differential effects on grammar learning outcomes and learner engagement remains limited. This study compares the effects of Kahoot!- and Quizizz-mediated grammar instruction on immediate recall, delayed retention, and self-reported learner engagement among Indonesian EFL learners at secondary level. Using a quasi-experimental three-group design Kahoot! condition, Quizizz condition, and conventional instruction control with ninety-three participants across eight weeks, the study finds that both game-based platforms significantly outperform conventional instruction on immediate recall, but that Quizizz produces stronger delayed retention advantages, likely attributable to its self-paced design and spaced review features. Engagement data from classroom observations and post-study interviews reveal important qualitative differences between the two platforms: Kahoot!'s real-time competitive atmosphere generates higher reported enjoyment during sessions but also greater test-like anxiety, while Quizizz's self-paced format produces lower peak excitement but more sustained engagement and greater willingness to attempt difficult items. The study draws on Game-Based Learning theory (Mayer, 2020; Plass et al., 2020) and the Desirable Difficulties framework (Bjork & Bjork, 2020) to argue that platform selection in EFL grammar instruction should be driven by instructional goals and learner profiles rather than by familiarity or availability, and that neither platform, used alone and unreflectively, is sufficient for deep grammatical knowledge development.